Synergy Between The Merdeka Belajar-Kampus Merdeka (Mbkm) Curriculum And Outcome-Based Education In Realizing An Excellent Graduate Profile - Fahrina Yustiasari Liriwati; Zulhimma Zulhimma (Systematic Literature Review Journal, 2025)
The implementation of the Merdeka Belajar-Kampus Merdeka (MBKM) curriculum and the Outcome-Based Education (OBE) approach represents a strategic response to the global challenges faced by 21st-century higher education. Both initiatives share the same goal: to produce graduates who are relevant to industry needs and capable of adapting to the times. This article aims to examine the synergy between MBKM policies and the OBE approach in the planning and implementation of higher education curricula to achieve excellent graduate profiles. This study uses a systematic literature review with a descriptive-qualitative approach. The findings indicate that integrating MBKM and OBE encourages universities to design outcome-based curricula with contextual learning rooted in real-world experience. Key success strategies include redesigning outcome-based lesson plans (RPS), cross-sector collaboration, and strengthening assessment systems. This article recommends reinforcing synergy among policymakers, lecturers, and external partners to promote adaptive and sustainable higher education.